Travailler au péril de sa santé - Lucie Goussard (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study looked at the various “masks” hiding the physical and mental difficulties of engineers’ work. It is based on qualitative research conducted in three large companies in the automobile, aeronautics, and energy sectors. In the examination of these difficulties, the study showed that the invisibility of these difficulties depended considerably on the quality of the employees’ work conditions as well as their educational and occupational socialization in a highly competitive environment. It likewise tried to determine the conditions needed to render the relations between health and work at the individual and collective levels visible. Finally, it showed how an activity that would primarily seem to engage cognitive and intellectual capacities also engaged the workers’ bodies. Their bodies bore the marks of the job’s difficulties, whether or not the constraints were physical or mental in nature, and forced the engineers to be aware of their pain when their limits were reached.